Synthesis, characterization, antimicrobial, and MOE evaluation of nano 1, 2, 4‐triazole‐based Schiff base ligand with some d‐block metal ions. (12th April 2021) - Mahmoud, Nessma F.; Abbas, Ashraf A.; Mohamed, Gehad G.
Abstract : Three new metal complexes of 4‐(benzylideneamino)‐5‐phenyl‐4H‐1, 2, 4‐triazole‐3‐thiol ligand (L) and three transition metal ions: Fe (III), Cu (II), and Zn (II) were synthesized and characterized. The ligand derived from 4‐amino‐5‐phenyl‐1, 2, 4‐triazole‐3‐thiol and benzaldehyde was synthesized in a 1:1 molar ratio. All the chelates were characterized by elemental analysis, conductivity measurements, thermal analysis, FT‐IR, and 1 H‐NMR spectroscopy. The IR spectrum revealed that the Schiff base ligand coordinated in a neutral bidentate manner with the metal ions through the azomethine N and thiol S. The thiol group coordinated to the metal ions without proton displacement as confirmed from the 1 H NMR spectra. The conductivity data showed the electrolytic nature of the Fe (III) and Cu (II) complexes while the Zn (II) complex was nonelectrolyte. All metal complexes had octahedral structure as depicted by spectral and elemental analyses. The complexes start decomposition at 35°C, and they decomposed in four to five steps. The scanning electron microscope (SEM) analysis confirmed the presence of metal complexes in nanostructure. The 1, 2, 4‐triazole Schiff base ligand (L) and its transition metal complexes have been screened for their antibacterial (Gram [+] bacteria): Bacillis subtilis and Staphylococcus aureus, (Gram [−] bacteria): Escherichia coli and Pseudomonas aeruginosa and two fungi: Candida albicans and Aspergillus flavus by agar diffusion method. The two metal complexes were subjected to molecular docking study against crystal structure of Aspergillus fumigatus (PDB ID: 6NE0) and crystal structure of Mycobacterium tuberculosis (PDB ID: 5UHF). The mode of binding between the A . fumigatus (PDB ID: 6NE0) and Mycobacterium tuberculosis strains and the complexes was discussed. Abstract : Three new metal complexes of 1, 2, 4‐triazole‐3‐thiol ligand (L) and three transition metal ions: Fe(III), Cu(II), and Zn(II) were synthesized in 1:1 ratio. They were characterized using elemental analysis, conductivity measurements, thermal analysis, FT‐IR, and 1 H‐NMR spectroscopy. The Schiff base ligand coordinated in a neutral bidentate manner with the metal ions through the azomethine N and protonated thiol S. All metal complexes had an octahedral structure as depicted by spectral and elemental analyses. The scanning electron microscope (SEM) analysis confirmed the presence of metal complexes in nano structure. The 1, 2, 4‐triazole Schiff base ligand (L) and its transition metal complexes were screened for their antibacterial and two fungi species by agar diffusion method. The two metal complexes were subjected to molecular docking study against crystal structure of Aspergillus fumigatus (PDB ID: 6NE0) and crystal structure of Mycobacterium tuberculosis (PDB ID: 5UHF).